As negociações coletivas de trabalho frente à reestruturação produtiva: um estudo do polo coureiro-calçadista paraibano a partir dos anos 1990 - Alves, Jorge Souza (2011)
This research examines the possible changes in collective labor bargaining, occurred in the leatherfootwear segment Paraiba, resulting from changes observed in this segment, from the year 1990. For this, we analyzed the agreements and the collective labor conventions, signed by three trade unions in the shoe industry of Paraiba, as well as interviews with union leaders to them. The results show that the technological and organizational changes implemented primarily by large companies, provided significant impact on labor relations that directly and indirectly contributed to change the shape and content of the negotiations, directly influencing, promoting and negotiating agreements and conventions that more flexible pay, hours and employment, and indirectly, because these innovations, as well as the flexibility of negotiated issues listed above, had some negative consequences for workers, as the breach of labor laws (with the creation of worker cooperatives fraudulent for example), the increase in working hours, occupational diseases (RSI/WMSD) and high turnover, so that unions acted at various times, in areas or fields hitherto little explored or never, but using the procedures or mechanisms already well known in the trade union as collective bargaining and, in some cases, using other forms of action such as lawsuits and labor stoppage. These events signaled, so the relevance of our assumptions and search that guided our research.